Exempting the university: Trigger warnings and intellectual space. Issue 2 (2nd July 2016) - Hickey, Jeremiah
Abstract: In the controversy over trigger warnings, authors tend to focus more on the warning rather than the trigger aspect of the debate. Trigger warnings serve as an important means to understand the nature of universities as well as how students, professors, and administrators view the university experience. I contend that trigger warnings should be seen as campus-wide interventions, not limited only to classrooms. After all, trauma can be triggered anywhere. This article argues that the trigger warnings controversy signifies the presence of an institutional crisis for universities, especially in relation to the allocation of resources necessary to help students suffering from trauma. Debating the use of trigger warnings is one thing; however, if students feel threatened or if they suffer trauma from controversial material, then the university needs to set aside resources to help students succeed.